Rancang Bangun Aplikasi Pendistribusian Sparepart Motor Berbasis Web - Ridwan Chijaya; Bernadus Gunawan Sudarsono; Helmy Daimon Matulessy; Fauziyah; Joseph (Fakultas Teknik, Universitas Bhayangkara Jakarta Raya, 2022)
CV. Wahana Baru is engaged in the distribution of spare parts specifically for two-wheeled vehicles. Wahana Baru has been established since 18 years ago or more precisely on March 29, 2003 with a name that has never changed, namely Wahana Baru. The business world that is lived in this modern era is very dependent on computerization which is growing and becomes a supporter in various activities within the company or organization. In distribution activities, a motorcycle spare part distribution system application is needed to make it easier for customers to order spare parts on CV. Wahana Baru to support activities is becoming more developed. To realize a motorcycle spare part distribution information system, a web-based motorcycle spare parts distribution information system application was designed at CV. New Rides. In defining requirements and analyzing system development, data collection methods were carried out by means of observation, interviews, and literature review from various sources of information. For the method of analysis and design using Unifield Modeling language (UML). The Motor Parts Distribution Information System uses the Hypertext Preprocessor (PHP) programming language and MySQL as its database. With the Motorcycle Spare Parts Distribution Information System, the processes involved in the distribution of motorcycle spare parts are easier to use, accurate, and integrated.